Pembinaan Dan Pelatihan Da’i Cilik Santri TK/TPA Al-Jihad - Lukman bin Juma, Nuratika B. Lukman; Nurwahidah; Nurul Islamiah; Mawaddah Warahma Ahmad (PENDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Guidance and training of da'i is an activity that can be done to introduce da'wah from an early age. Da'wah is an obligation for every Muslim, so it must be learned and nurtured from childhood. The younger generation is a superior seed who can continue the da'wah struggle, which can be started from the children who are members of the Kindergarten/TPA students. The purpose of this coaching and training activity is to provide an understanding of da'wah materials, train public speaking skills from a young age, and provide training to become a small preacher so that they can benefit the community. The approach method used in the implementation of this activity is observation, socialization, implementation of activities, and evaluation. After the training, TK/TPA students have the ability to convey da'wah well even though in a not broad scope. In addition, more or less have trained children's confidence to speak in public.